2021
DOI: 10.1371/journal.pone.0254230
|View full text |Cite
|
Sign up to set email alerts
|

Routine health information utilization and associated factors among health care workers in Ethiopia: A systematic review and meta-analysis

Abstract: Background Utilization of routine health information plays a vital role for the effectiveness of routine and programed decisions. A proper utilization of routine health information helps to make decisions based on evidence. Considerable studies have been done on the utilization of routine health information among health workers in Ethiopia, but inconsistent findings were reported. Thus, this study was conducted to determine the pooled utilization of routine health information and to identify associated factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 26 publications
7
31
2
Order By: Relevance
“…In this study, information use practice was less likely among trained health workers compared to untrained health workers. This nding was in contradiction to other studies that found RHI training was positively associated with proper information utilization (17,20,24,26,27,29). In the study area, the majority of health workers were trained, with a higher proportion of them having received training before the 12 months survey period.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, information use practice was less likely among trained health workers compared to untrained health workers. This nding was in contradiction to other studies that found RHI training was positively associated with proper information utilization (17,20,24,26,27,29). In the study area, the majority of health workers were trained, with a higher proportion of them having received training before the 12 months survey period.…”
Section: Discussioncontrasting
confidence: 99%
“…Access to good quality data in turn in uences better utilization of information. This nding was supported by other studies that showed health workers' knowledge of RHI management was associated with good information utilization (17,20).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations